Coping with the COVID-19 crisis: an overview of service adaptation and challenges encountered by a rural Psychiatry of Later Life (POLL) team. (2nd December 2021) - Usman, M.; Fahy, S.
Abstract : The COVID-19 pandemic has posed many challenges in maintaining standards of care and treatment for patients while managing the increased anxieties of patients, carers and the public in general. This paper highlights several clinical, administrative, medicolegal and IT implications of COVID-19 on the delivery of mental healthcare to an elderly vulnerable patient cohort due to recommended social distancing measures. Our Psychiatry of Later Life team has adapted to this by restricting face-to-face consultation, while continuing to provide telephone support. We have modified our documentation standard and have improved some aspects of our team working by facilitating flexible working arrangement and relevant training for staff as well as by embracing new technology. Notwithstanding the challenges therefore, this exceptional time has also opened avenues for new and innovative opportunities that can be further explored even when the current crisis eventually passes.